Soaring Imaginations: The First Montgolfier Ballooning Spectacle at Versailles in Word and Image - Lewis Theobald, Catherine (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
Beginning with the first series of flights by the French Montgolfier brothers in 1783, hot air ballooning quickly metamorphosed from a dangerous scientific experiment with potential military uses into a widespread cultural craze with deep social implications. Using the lens of the idea of “wonder,” I examine the word-image interactions in a selection of engraved representations of the first Montgolfier demonstration for Louis XVI at Versailles. Such a collective close reading first exposes techniques that aim at encouraging admiration in readers for both the new technology and the French state that produced it. However, visual cues in the images indicate a persistent suggestion of doubt and uncertainty—and even fear—as they take readers “up and away” from the confines and comforts of everyday life. The word-image nexus surrounding this spectacle generates an altered textual world in which traditional social and sexual hierarchies lose stability and the future is full of possibility.